Left ventricular myocardial strain quantification with two- and three-dimensional cardiovascular magnetic resonance based tissue tracking - Qu, Yang-Yang; Paul, Jan; Li, Hao; Ma, Gen-Shan; Buckert, Dominik; Rasche, Volker (Quantitative imaging in medicine and surgery, 2021)
Cardiovascular magnetic resonance based tissue tracking (CMR-TT) was reported to provide detailed insight into left ventricular (LV) contractile function and deformation with both of two- and three-dimensional (2/3D) algorithms. This study was designed to investigate the feasibility and reproducibility of these two techniques for measuring LV global and segmental strain, and establish gender- and age-related reference values of global multi-dimensional peak strains among large healthy population. We retrospectively recruited 150 healthy volunteers (75 males/females) and divided them into three age groups (G , G and G ). LV global mean and peak strains as well as segmental strains in radial, circumferential and longitudinal directions were derived from post-hoc 2/3D CMR-TT analysis of standard steady-state free precession (SSFP) cine images acquired at 1.5T field strength. Both 2D and 3D CMR-TT modalities enable the tracking of LV myocardial tissues and generate global and segmental strain data. By comparison, 3D CMR-TT was more feasible in measuring segmental deformation since it could generate values at all segments. The amplitudes of LV 3D global peak strain were the smallest among those of 2/3D corresponding global mean or peak strains except in the radial direction, and was highly correlated with 2D global mean strains (correlation coefficient r=0.71-0.90), 2D global peak strains (r=0.75-0.89) and 3D global mean strains (all r=0.99). In healthy cohort, LV 3D global peak values were 44.4%±13.0% for radial, -17.0%±2.7% for circumferential and -15.4%±2.3% for longitudinal strain. Females showed significantly larger amplitude of strains than males, especially in G (P<0.05). The subjects in G showed larger amplitude of strains than the volunteers in younger groups. The intra- and inter-observer agreement of 2/3D CMR-TT analysis in evaluating LV myocardial global deformation was better than segmental measurement. CMR-TT is a feasible and reproducible technique for assessing LV myocardial deformation, especially at the global level. The establishment of specific reference values of LV global and segmental systolic strains and the investigation of dimension-, gender- and age-related differences provide a fundamental insight into the features of LV contraction and works as an essential step in clinical routine.